Some Results of Forecast of Hydrodynamic Processes in the Easternmost Part of the Black Sea - Kordzadze, Avtandil A.; Demetrashvili, Demuri I.; Demetrashvili, Demuri I. (Journals of Georgian Geophysical Society, 2017)
Regional forecasting system to predict currents, temperature and salinity 3-D fields for the easternmost part of the Black Sea have been developed within the context of the international scientific-technical EU projects ARENA and ECOOP. The regional area is bounded with the Caucasus and Turkish shorelines and the western liquid boundary coinciding with 39.360E. A core of the forecasting system is the highly resolving 3-D regional prognostic model of the Black Sea dynamics developed at M. Nodia Institute of Geophysics. The regional model with 1 km spacing is nested in the basin-scale model of the Black Sea dynamics (with the grid step 5 km) of Marine Hydrophysical Institute (MHI, Sevastopol/Ukraine). All input data required for 4-days forecasts are regularly obtained from MHI via Internet. At present the system is ready for operational functioning.